A Study on the Entrepreneurial Behviour of Members among Woman Self Help Groups in Srivilliputtur Taluk - R. , Selvakumar; S. , Karthik; P. , Ramakrishnan (International Journal of Psychosocial Rehabilitation, 2020)
There are two problems, like poverty and unemployment, which lead to mainly focusing on the importance of small-scale industries like agriculture and rural-based industries and mainly concentrating on developing the field of entrepreneurship. Women in our country play a very important role from beginning to end in the development of their resourcefulness and their skills. But in this male-dominated society, they are facing many problems to prove themselves as resourceful and skillful. Animators are acting as leaders who motivate and guide the members and help run the SHGs effectively. Therefore, it is a platform through which the women in our country can develop not only skills but also increase the status and empowerment of women financially, legally, socially, economically, and politically in the society. This study is an attempt to analyze the various levels of entrepreneurial skills and identify the main need for getting a loan from the group with the help of the Garrett ranking method. The result shows that the majority of skills possessed by the members of SHGs are self-confidence, decision-making, planning, goal achievement, and motivation.